2005
DOI: 10.1158/0008-5472.can-04-3931
|View full text |Cite
|
Sign up to set email alerts
|

Stem and Progenitor-Like Cells Contribute to the Aggressive Behavior of Human Epithelial Ovarian Cancer

Abstract: The cellular mechanisms underlying the increasing aggressiveness associated with ovarian cancer progression are poorly understood. Coupled with a lack of identification of specific markers that could aid early diagnoses, the disease becomes a major cause of cancer-related mortality in women. Here we present direct evidence that the aggressiveness of human ovarian cancer may be a result of transformation and dysfunction of stem cells in the ovary. A single tumorigenic clone was isolated among a mixed population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
620
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(656 citation statements)
references
References 20 publications
26
620
2
8
Order By: Relevance
“…The existence of ovarian cancer-initiating cells was previously supported by others in studies whereby cancer cells isolated from ascitic fluid of ovarian cancer patients exhibited characteristics consistent with those expected of a cancer stem cell (Bapat et al, 2005;Szotek et al, 2006). More recently, CD44 þ ovarian cancer cells have been shown to possess cancer-initiating capabilities (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…The existence of ovarian cancer-initiating cells was previously supported by others in studies whereby cancer cells isolated from ascitic fluid of ovarian cancer patients exhibited characteristics consistent with those expected of a cancer stem cell (Bapat et al, 2005;Szotek et al, 2006). More recently, CD44 þ ovarian cancer cells have been shown to possess cancer-initiating capabilities (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…In vivo, ovarian SP cells have the potential to initiate tumor growth more quickly and at lower cell numbers than non-SP ovarian cancer cells [165]. Moreover, cell clones with sustained clonogenic potential in vitro and tumorgenicity in vivo, even after serial transplantation in mice, have been identified in ovarian cancer [16]. The possible multipotency of such clones was further supported by the expression of three "stemness" markers: Oct4, Nanog, and Nestin [16].…”
Section: Ovarian Cancer: Pluripotency and Putative Cscsmentioning
confidence: 99%
“…Moreover, cell clones with sustained clonogenic potential in vitro and tumorgenicity in vivo, even after serial transplantation in mice, have been identified in ovarian cancer [16]. The possible multipotency of such clones was further supported by the expression of three "stemness" markers: Oct4, Nanog, and Nestin [16]. More recently, Ferrandina et al [50] identified the expression of CD133 antigen, considered to be a marker of undifferentiated cells, in a cellular subpopulation in a large variety of ovarian tissues.…”
Section: Ovarian Cancer: Pluripotency and Putative Cscsmentioning
confidence: 99%
“…In the second part of the study, we used an in vitro model developed earlier by us that comprises 19 single-cell clones isolated from the ascites of an ovarian serous adenocarcinoma patient (Bapat et al, 2005). Of these, one clone was tumorigenic (A2); another one (A4) underwent a spontaneous transformation in vitro, whereas the remaining 17 clones were non-tumorigenic.…”
Section: Primary Tissue Samples and Cell Culturesmentioning
confidence: 99%